In vitro Effects of Bacterial Exposure on Secretion of Zonulin Family Peptides and Their Detection in Human Tissue Samples - Jian, Ching; Kanerva, Sonja; Qadri, Sami; Yki-Järvinen, Hannele; Salonen, Anne (Frontiers in Microbiology, 2022)
Commercially available enzyme-linked immunosorbent assays (ELISAs) for zonulin (pre-haptoglobin 2), a protein with tight junction regulatory activity in the epithelia, were recently shown to recognize other proteins that are structurally and functionally related to zonulin, termed zonulin family peptides (ZFPs). With little or no information about the identity and property of ZFPs, various commercial zonulin ELISA kits are widely utilized in research as a marker of intestinal permeability. Bacterial exposure is a known trigger for the secretion of zonulin, but it remains unclear whether distinct bacteria different in their capability to stimulate zonulin secretion. We hypothesized that ZFPs are similar to zonulin regarding response to bacterial exposure, and aimed to compare the effects of non-pathogenic, gram-negative bacteria (Escherichia coli RY13 & E. coli K12 DH5α) and probiotic, gram-positive bacteria (Lactobacillus rhamnosus GG & Bifidobacterium bifidum) on ZFP secretion in an in vitro model. Additionally, utilizing samples from human clinical trials, we correlated circulating levels of ZFPs to the gut bacteria and determined the presence of ZFPs in various human tissues. Unexpectedly, we found that the ZFPs quantified by the widely used IDK® Zonulin ELISA kits are specifically triggered by the exposure to live Lactobacillus rhamnosus GG in HT-29 cells, associated with absolute abundances of intestinal Lactobacillus and Bifidobacterium in adults, and are copious in the small intestine but undetectable in the liver or adipose tissue. These characteristics appear to be different from zonulin, and highlight the need for further characterization of ZFPs recognized by commercially available and widely used “zonulin” ELISAs.